New technology for oil-free compressed air.
Oil contamination in compressed air can greatly affect production as it can cause product waste, recall or quality control issues, and a single test can cost up to EUR 3000. An EU-funded project came up with a new cost-effective solution for monitoring contaminants in compressed air that eliminates labour-intensive sampling and laboratory analysis.